Cholangio - digestive mediate bypass: Venipuncture catheter bridge - Balboa, Oscar; Voelker, Ricardo; Geninazzi, Héctor; Lerena, Ana (Cirugía del Uruguay, 1979)
Report of a technique for mediate cholangio - digestive derivation with polyethyiene tube of the type used for venous puncture. It is simple, quick and efficient.